Men in the Nursery: Gender and Caring Work - Cameron, Claire; Moss, Peter; Owen, Charlie (SAGE Publications, 1999)
This book brings together what is currently known about men working in childcare settings. The authors consider the issues involved in gender and childcare, look at the structure of early childcare services in the UK and European contexts, and consider how men came to work in childcare settings. Further chapters explore parents′ views, staff dynamics and child protection issues. The voices and views of childcare workers are heard throughout this unique book.